Pembelajaran Menulis Teks Narasi dengan Metode Mind Mapping pada Siswa MI - Munjayana, Siti (FONDATIA, 2024)
The purpose of this study was to determine the skills of writing narrative texts using the mind mapping method for fifth grade students of MI Muhammadiyah Al Qomariyah Wates Boyolali at the pre-writing, during writing, and post-writing stages. The research method used descriptive qualitative. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing/verification. The results showed that the application of mind mapping method contributed positively to the improvement of students' skills in writing narrative text. The learning phases carried out include pre-writing stage activities, during writing, and post-writing, successfully achieving satisfactory results, with grade V students of MI Muhammadiyah Al Qomariyah Wates Boyolali successfully obtaining a very good category with a score of 90.0 and a class average of 82.7. This research is expected to be a reference for MI teachers to use the mind mapping method in learning activities to write narrative texts.